Nonoscillation theorems for functional differential equations of arbitrary order - John R. Graef; Myron K. Grammatikopoulos; Yuichi Kitamura; Takasi Kusano; Hiroshi Onose; Paul W. Spikes (International Journal of Mathematics and Mathematical Sciences)
The authors give sufficient conditions for all oscillatory solutions of a sublinear forced higher order nonlinear functional differential equation to converge to zero. They then prove a nonoscillation theorem for such equations. A few intermediate results are also obtained.